Hangover resistance in a Canadian University student population. (June 2017) - Kruisselbrink, L. Darren; Bervoets, Adriana C.; de Klerk, Suzanne; van de Loo, Aurora J.A.E.; Verster, Joris C.
Abstract: Background: Resistance to alcohol hangover may be a risk factor for alcohol use disorder. Previous research to establish the prevalence of hangover resistance in a drinking population has either not used comparable intoxication levels or has considered hangover resistance over a limited time frame. The purpose of this study was to examine the prevalence of lifetime hangover negative (LHN) drinkers across comparable eBAC values ranging from 0 to 500 mg/dl. Methods: Students at an eastern Canadian university were surveyed about their heaviest drinking episode in the past month and indicated whether they had ever experienced a hangover in their lifetime (LHN) and, if they had, the hangover severity they experienced the next day. eBACs were calculated and the percentage of LHN drinkers was computed at each 10 mg/dl eBAC increment from 0 to 500 mg/dl. Results: Most LHN drinkers (58% female, 71% male) had an eBAC on their heaviest drinking occasion below 80 mg/dl. Above eBACs of 80 mg/dl, 5.8% of female and 5.1% of male drinkers were lifetime hangover negative. Conclusions: The results suggest that only a small percentage of heavy drinkers lay claim to being lifetime hangover negative. Highlights: The estimated BAC of more than half of male and female lifetime hangover negative drinkers was below 80 mg%. Approximately 5% of drinkers registering estimated BAC's beyond 80 mg% claim to be lifetime hangover negative. Biological and psychological hypotheses are proposed to explain why heavy drinkers may be lifetime hangover negative.